Answer:
y = C/h - 2
Step-by-step explanation:
Equation
C = (2 + y)*h
Solution
C = (2 + y)*h Divide by h
C/h = (2 + y)*h/h
C/h = 2 + y Subtract 2 from both sides
C/h-2 = 2-2+ y Combine
C/h - 2 = y
Answer: 10
Step-by-step explanation:
25 + 20= 45
45 + ? = 6:00
A= 15
Tienes k poner números juntos, este esta igual como una pregunta de jj di x
So find g(0) and g(3)
G(0) = 0^2 -5(0) +3 = 3
And g(3) = 3^2 - 5(3) +3 = 9 - 15 + 3 = 3 so there is no change in g(x) for that interval.
H(0) = 8(0) + 10 = 10
And h(3) = 8(3) + 10 = 34
So the change in h(x) for that interval is 24.